What do leaders really do? getting under the skin of what makes a great leader tick - Grout, Jeff. (Chichester Capstone, 2007)
An enormous range of literature on leadership and management theory has been produced over the years, some of it highly academic and much of it contradictory. What Do Leaders Really Do? takes the basis of the best-known management theories to see how they fit with the practical reality of leadership. How do leaders spend their time? Are they really preoccupied with strategy, vision and inspiring people? Do they lead by accident, or design? The book challenges the assumption that leaders are born, not made and explores the theory that female leaders are fundamentally different from their male counterparts.
Includes bibliographical references (p. [202]-203) and index.
Keywords: Leadership